1987
DOI: 10.1002/jcb.240340407
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of epidermal growth factor‐stimulated DNA synthesis by a bovine sialoglycopeptide inhibitor occurs at an intracellular level

Abstract: The control of cell proliferation involves the complex interaction between growth factors and growth inhibitors. We have examined this interaction with the mitogen epidermal growth factor (EGF) and a recently purified 18 kD, pI 3, sialoglycopeptide that reversibly inhibits cellular metabolism of a variety of cells. The sialoglycopeptide was a very potent inhibitor of EGF action; 0.22 nM of the inhibitor completely blocked the mitogenic effect of 1.60 nM of EGF. The sialoglycopeptide, however, did not affect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…These studies must be interpreted with caution, however, since the compounds utilized to block various intracellular calcium changes may have other, as of yet unknown, effects on cellular constituents. Previous studies in our laboratory have demonstrated the ability of the CeReS-18 growth inhibitor to inhibit the induction of DNA synthesis mediated by such growth factors (Bascom et al, 1987;Johnson and Sharifi, 1989). In addition, reports by Takuwa et al (1992Takuwa et al ( , 1993 demonstrated that stimulation of the phosphorylation of the retinoblastoma gene product (Rb) and activation of p34cdc2 kinase are calciumicalmodulin-dependent processes.…”
Section: Ceres-18mentioning
confidence: 93%
See 2 more Smart Citations
“…These studies must be interpreted with caution, however, since the compounds utilized to block various intracellular calcium changes may have other, as of yet unknown, effects on cellular constituents. Previous studies in our laboratory have demonstrated the ability of the CeReS-18 growth inhibitor to inhibit the induction of DNA synthesis mediated by such growth factors (Bascom et al, 1987;Johnson and Sharifi, 1989). In addition, reports by Takuwa et al (1992Takuwa et al ( , 1993 demonstrated that stimulation of the phosphorylation of the retinoblastoma gene product (Rb) and activation of p34cdc2 kinase are calciumicalmodulin-dependent processes.…”
Section: Ceres-18mentioning
confidence: 93%
“…CeReS-18 binds to a specific cell surface receptor (Sharifi and Johnson, 1987), and binding to this receptor correlates with protein synthesis inhibition (Bascom et al, 1986).…”
mentioning
confidence: 99%
See 1 more Smart Citation